The Observational Learning Effect on Skill Acquisition in Football - WenLang Huang; ShaoYong Liu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The primary goal of this research is to discuss the observational learning effect on skill acquisition in football. A critical research study based on preliminary data is collected through online surveys, questionnaires, and observations from football coaches, football participants, and audiences watching football games with a passion. The nature of this study is quantitative research. The data was analyzed Descriptive statistics, correlation and regression techniques, One-way ANOVA test, run on SPSS software, and test the hypotheses. According to regression and descriptive statistical analysis, the research findings indicate that some indicators show positive and significant relation and some negative and insignificant related to football players' observational learning. In this research, we examine all players' observational learning on skill acquisition in football. Our findings suggested that observational learning, attention, Retention, production processes, and motivational factors are influence positively and significantly on skill acquisition in football. Results show that these variables influence skill acquisition in football players and enhance performance. This observational learning attracts thousands and millions of people. There is a significant relationship between observational learning and skill acquisition in football.